1993
DOI: 10.1002/gps.930081109
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity among ‘ABLE’ residents of part III homes

Abstract: SUMMARYOne hundred and thirty residents of 11 Part 111 homes who had been in care for a year or more and had no cognitive impairment as assessed by the Crichton Royal Behavioural Rating Scale were investigated using the Clinical Interview Schedule, the 10-question Mental Test Score and standardized schedules for aphasia and parietal lobe function. Thirty per cent showed signs of early dementia; mild to moderate neurotic symptoms were common among the remainder. Ten per cent had longstanding impairment of intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Rates of depression discovered here were much lower than reported in previous studies using the BAS (Ames et al, 1988;Mann et al, 1984;Ames, 1991). Similarly, Stout et al (1993) found only 15% of non-confused residents in Part I11 homes to show evidence of affective disorder. Such low rates of depression found in this study may reflect the changing nature of EPHs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rates of depression discovered here were much lower than reported in previous studies using the BAS (Ames et al, 1988;Mann et al, 1984;Ames, 1991). Similarly, Stout et al (1993) found only 15% of non-confused residents in Part I11 homes to show evidence of affective disorder. Such low rates of depression found in this study may reflect the changing nature of EPHs.…”
Section: Discussionmentioning
confidence: 96%
“…The development of affective symptoms may be a reaction to such factors, which remain unresolved by admission to residential care. Facets of life in residential care may in themselves precipitate and perpetuate depression (Stout et al, 1993). Such people are perhaps now being managed by support at home and are not therefore entering residential care.…”
Section: Discussionmentioning
confidence: 99%
“…While there are interesting and innovative programs in both the UK (Handysides, 1993) and the US (Rovner et al, 1996), research in both countries has shown that mental illness in nursing homes is common yet usually goes undetected, and even when detected usually goes untreated (Stout et al, 1993;Rovner and Katz, 1993). Also, UK colleagues expressed concern about career structure and training for residential care sta.…”
Section: Mental Health Servicesmentioning
confidence: 95%
“…The evidence suggests that the influence of length of time in care is different for cognitively impaired residents, and more likely to be a negative for the well-being of those without cognitive impairment (Stout et al ., 1993; Pot et al ., 2005). Many residents admitted with dementia have undiagnosed depression (Sheehan et al ., 2007), which is likely to improve if diagnosed and treated on and after admission (Masand, 1995; Payne et al ., 2002).…”
Section: Etiology Of Depressionmentioning
confidence: 99%